Features of Argumentation in Classical Rhetorical Studies (Between Practice and Theory) - rahmun, salem; boumasha, larbi (El Omda in Linguistics and Discourse Analysis, 2022)
Argumentation in the contemporary era is undoubtedly one of the outcomes of pragmatic theory. However, this does not imply neglecting its roots in Arabic rhetorical tradition, as it is shared by multiple disciplines such as exegesis, theology, Qur’anic studies, and principles of Islamic jurisprudence. Its origins in Arab heritage can be traced back to rhetoric (khitāba), which in pre-Islamic times constituted one of the most important persuasive and influential means of addressing audiences, second only to poetry. This study examines the efforts of classical Arab rhetoricians in uncovering the dimensions of argumentation theory, particularly Al-Jahiz and his theory of البيان (expression/clarity), as well as what is found in rhetorical works that emphasize context (maqām), addresser, and addressee as fundamental elements through which persuasive strategies are realized.